New records of Phaseolus microcarpus (Leguminosae: Phaseoleae) for Costa Rica - Debouck, Daniel G.; Chaves-Barrantes, Néstor Felipe; Araya Villalobos, Rodolfo (2019)
Evidence is presented about the presence of Phaseolus microcarpus in Costa Rica, while it was previously reported northwards in other Central American countries and Mexico. Fourteen populations are currently known, four from the Peninsula of Nicoya, and ten are in the tropical dry forest of the mainland of this country.